How to survive in the North - Healy, Luke (2016)
"Weaving together the true life historical expeditions of Ada Blackjack and Robert Bartlett with a contemporary fictional story, How to Survive in the North is a unique and visual narrative journey that shows the strength it takes to survive in even the harshest conditions--whether that be struggling for survival in the Arctic in the 1900s or surviving a mid-life crisis in the present day"--
Keywords: Bartlett, Bob, -- 1875-1946 -- Comic books, strips, etc; Blackjack, Ada, -- 1898-1983 -- Comic books, strips, etc; College teachers -- Comic books, strips, etc; Midlife crisis -- Comic books, strips, etc; Arctic regions -- Discovery and exploration -- Comic books, strips, etc; Comics (Graphic works); Graphic novels